Microstructure and mechanical properties of Ti65 titanium alloy T-joints welded by dual-beam laser - Xiaolong Lv; Guodong Li; Kaiming Wang; Hanguang Fu (Journal of Materials Research and Technology, 2025)
This study systematically characterized the microstructure, phase transformation, and mechanical properties of Ti65 titanium alloy T-joints welded using dual-beam laser with Ti65 welding wire as filler. The welded joint exhibits distinct zones: the base material retains a fine duplex α-phase microstructure; the heat-affected zone (HAZ) shows grain coarsening and phase transformation; and the fusion zone (FZ) forms needle-like α′ martensite due to rapid cooling-induced β-phase transformation. Elemental analysis confirms uniform alloy distribution with no segregation. X-ray diffraction (XRD) reveals that the fusion zone comprises predominantly α′ martensite (76.79 %) with a minor β phase. Electron backscatter diffraction (EBSD) demonstrates grain refinement and a high proportion of high-angle grain boundaries in the fusion zone, enhancing strength and crack resistance. Tensile testing indicates high strength (723–779 MPa) but limited ductility (1.3–1.5 % elongation). Hardness decreases gradually from the fusion zone to the skin zone, with fine-grain strengthening significantly increasing fusion zone hardness. These findings demonstrate that dual-beam laser welding with Ti65 filler wire effectively refines microstructure and enhances mechanical properties, addressing critical challenges in welding high-performance titanium alloys.